ACCESS TO EDUCATION FOR ETHNIC MINORITY CHILDREN IN GEORGIA (IMERETI REGION) - Marekhi Nikoladze (International Journal of Innovative Technologies in Social Science, 2024)
For representatives of ethnic minorities living in Georgia, general education and knowledge of the state language is one of the ways of civil integration, which promotes their participation in political and public life. In this process, a special role is assigned to the school. The priorities of teaching the state language for non-Georgian language schools are outlined in various international and local documents, and among them it is important to single out the "State Strategy of Civil Equality and Integration 2015-2020". This document aims to promote civic and political participation of ethnic minorities, encourage and promote cultural diversity, increase access to quality education, and improve proficiency in the state language. Ethnic minorities often face serious threats, discrimination and racism in terms of access to education, which deprives them of the opportunity to exercise the right to education on an equal footing with the majority.